Persistent symptoms in agricultural workers exposed to organophosphate pesticides - Martha E. Palacios N; María P. Paz (Universidad de Antioquia, 2011)
Objective: to evaluate the prevalence of these symptoms and their relationship with pesticide exposure and the cholinesterase levels in agricultural workers. Methodology: an analytical cross-sectional study conducted in Mexico. Cholinesterase concentration and symptom frequency were assessed for 106 agricultural workers. Exposure was defined with a composed index of 15 variables. Results: symptom prevalence was 52 out of 100 workers. 31% of workers had 1 to 3 of the symptoms, 16% had 4 to 9 of them and 5% had 10 or more of the symptoms. There was an association, p = 0.03, between days of exposure and persistent symptoms. Likewise, there was an association between exposure level and the presence of probable and specific symptoms. Patients with the highest exposure level had 20% more chances of exhibiting symptoms. Cholinesterase concentration ranges were normal. Anemia was detected in 28% of the population. It was three times as frequent in females as in males (p < 0.001). Conclusions: it was possible to identify the increase of persistent symptoms in workers with cholinesterase levels that are usually considered to be normal.